A critical review on phytochemical profile and health promoting effects of mung bean (Vigna radiata) - Kumar Ganesan; Baojun Xu (Food Science and Human Wellness)
The seeds and sprouts of mung bean are very common cruise in Asia. Evidence showed that bioactive compounds in mung bean have emerged as an increasing scientific interest due to their role in the prevention of degenerative diseases. All data of in vitro, in vivo and clinical studies of mung bean and its impact on human health were collected from a library database and electronic search. Botanical, phytochemical and pharmacological information was gathered and orchestrated. Remarkable studies have been demonstrated, showing the enhancement of metabolites in mung bean during the sprouting process, which possesses various health benefiting bioactive compounds. These compounds have been frequently attributed to their antioxidant, anti-diabetic, antimicrobial, anti-hyperlipidemic and antihypertensive effect, anti-inflammatory, and anticancer, anti-tumor and anti-mutagenic properties. In this critical review, we aimed to study the insight of the nutritional compositions, phytochemistry, and health-promoting effects of mung bean and its sprouts. The various curative potential of mung bean provides successive preclinical outcomes in the field of drug discovery and this review strongly recommends that mung bean is an excellent nutritive legume, which modulates or prevents chronic degenerative diseases. Keywords: Mung bean, Nutritional composition, Phytochemistry, Health promoting effects